(untitled) (International Seven Journal of Multidisciplinary, 2025)
Micro and small companies play a fundamental role in the global economy. However, many of them face significant challenges that lead to their premature closure. This review article explores the main causes of mortality in micro and small companies, providing information designed to help entrepreneurs overcome obstacles and promote the sustainability of their enterprises. The bibliographic research presented here adopted a qualitative approach to the data obtained. The central conclusion reached after the analysis is that the early mortality of micro and small companies cannot be attributed to a single internal or external factor, as these elements are interconnected and contribute to the success or failure of the business.